ANALISIS FAKTOR-FAKTOR PERUSAHAAN YANG MEMPENGARUHI KINERJA EKSPOR (Studi Kasus Perusahaan Ekspor Di Provinsi Lampung Model Komparasi) - Andy Fitriyadi Dharma Tilaar (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2012)
Globalization will bring opportunities for the companies to enter foreign market. However, tosuccess in that kind of market it will depends on some factors. This study try to find out what factorsbasically contribute to the success of companies in Lampung in entering international market.Using twenty seven companies that involved in exporting activities in Lampung, the study found outthat statistically internal and external factors do have contribute to the firms’s export performance.Moreover, this study among others conclude that government should play their roles in creatingconducive atmosphere for the business sectors by reducing high cost economy. Limitations,suggestions and implication of this research are also discussed